Swedish rape legislation from use of force to voluntariness - critical reflections from an everyday life perspective - Bladini, Moa (Bergen journal of criminal law & criminal justice, 2020)
After decades of debate and reforms on the rape legislation, a shift from a use of force-based into a consent-based rape offence (with voluntariness as the decisive criteria) entered into force in Sweden in July 2018. The aim of this article is to review and critically analyse Swedish statutory regulation of rape, starting in the historical development and debates as a backdrop. The authors take their starting point in critique put forward within the field of feminist legal studies and uses an everyday life perspective to examine some of the assessments made in the preparatory work in the decisions made on how to best protect the individual’s right to personal and sexual integrity and sexual self-determination. The analysis shows that a male rationale permeates the preparatory works and points at a need for further research on the criterion of voluntariness and its presumptions on autonomy.